Serum vitamin levels in multiple system atrophy: A case-control study - Chen, Daji; Wan, Linlin; Chen, Zhao; Yuan, Xinrong; Liu, Mingjie; Tang, Zhichao; Fu, You; Zhu, Sudan; Zhang, Xuewei; Qiu, Rong; Tang, Beisha; Jiang, Hong (Frontiers in Aging Neuroscience, 2023)
Aim There is increasing evidence suggesting that vitamins may play important roles in the pathogenesis of multiple system atrophy (MSA). The purpose of this study was to detect the changes of serum vitamin levels and investigate their correlation with disease severity in MSA patients. Methods In this cross-sectional study, 244 MSA patients, 200 Parkinson’s disease (PD) patients and 244 age-gender matched healthy controls were recruited. Serum vitamin levels were measured, including vitamin A, B1, B2, B9 (folate), B12, C, D, and E. Relevant clinical scales were used to assess the disease severity of MSA patients. Results Compared with the healthy controls, decreased serum folate levels and increased serum vitamin A and C levels were detected in MSA patients. Similar differences were also observed in the gender-based subgroup analysis. There were no differences detected between MSA and PD patients. In MSA patients, significant correlation was found between vitamin A, folate, or vitamin C and relevant clinical scales or laboratory findings. In addition, ROC analysis showed potential diagnostic value of the combination of vitamin A, folate, and vitamin C in distinguishing MSA patients from healthy controls. Conclusion There were significant changes in the blood vitamin spectrums of MSA patients, suggesting that dysregulation of vitamins homeostasis might play an important role in the pathogenesis of MSA.